2018
DOI: 10.1021/acs.jafc.8b04243
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Long Noncoding RNAs Expressed during Intramuscular Adipocytes Adipogenesis in Fat-Type and Lean-Type Pigs

Abstract: The meat quality of local breed pigs is more tender and juicier than the imported varieties. The important reason is that the intramuscular fat content is high. Even through modest sequence conservation and evolution, the expression pattern and function of long noncoding RNAs (lncRNAs) seem to be conserved. In spite of that, analysis of lncRNAs associated with intramuscular fat development remains unknown to us in porcine. Here, we systematically investigated lncRNAs of intramuscular adipocytes of fat local Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
(43 reference statements)
1
36
0
Order By: Relevance
“…With regards to intramuscular fat accumulation, adipocyte proliferation and differentiation are two important factors that contribute to lipid deposition [27]. In previous studies, lncRNAs were found to exert a regulatory role in the proliferation of porcine intramuscular adipocytes [9]. Our study showed that lncRNA may also modulate the adipogenic process of intramuscular adipocytes.…”
Section: Lnc_000368 Promotes Intramuscular Adipocyte Differentiationsupporting
confidence: 54%
See 1 more Smart Citation
“…With regards to intramuscular fat accumulation, adipocyte proliferation and differentiation are two important factors that contribute to lipid deposition [27]. In previous studies, lncRNAs were found to exert a regulatory role in the proliferation of porcine intramuscular adipocytes [9]. Our study showed that lncRNA may also modulate the adipogenic process of intramuscular adipocytes.…”
Section: Lnc_000368 Promotes Intramuscular Adipocyte Differentiationsupporting
confidence: 54%
“…Moreover, PU.1 AS lncRNA has also been found to promote adipogenic differentiation in porcine intramuscular adipocytes [8]. Furthermore, lncRNAs were differentially expressed in pig breeds with differing IMF contents [9]. These studies indicate that lncRNAs may be critical modulators in porcine IMF accumulation, thus potentially providing novel breeding selection markers that select for improved pork quality.…”
Section: Introductionmentioning
confidence: 89%
“…AQ pigs, one Chinese fat-type pig breed, have high good meat quality and slow growth rate [23]. Whereas the Chinese domestic breed has the universal characteristics of higher fat deposition capacity compared to that with Western commercial pig breeds [24]. Accordingly, the two pig breeds can be taken as ideal animal models to comparatively study the mechanisms controlling adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although several lincRNAs have been reported associated with pork and poultry IMF [12][13][14][15], little is known about the mechanism of lincRNA gene regulation in pig IMF.. The objectives of this work were to perform RNA sequencing analysis using an IMF character segregation population which construct using high IMF pigs (Min pig) and low IMF pigs (Large white pigs) crossbred and to analyze the joint or independent effects of lincRNAs on IMF.…”
Section: Introductionmentioning
confidence: 99%